Evaluation of Electronic Medical Record System Implemen-tation in Outpatient Services at RSUD Weda - Syahrul Syahrul; Wahyu Wijaya Widiyanto (International Journal of Health and Social Behavior, 2025)
The implementation of Electronic Medical Records (EMR) in healthcare institutions aims to improve the efficiency, accuracy, and accessibility of medical data. RSUD Weda, a regional hospital in Indonesia, has adopted an EMR system in its outpatient services to replace conventional manual processes. However, this transition has faced several challenges, including inadequate training, unstable network infrastructure, and inconsistent adherence to Standard Operating Procedures (SOPs). This study aims to evaluate the performance of the EMR implementation using a qualitative descriptive method based on the 5M framework—Man, Material, Machine, Method, and Money. Data were collected through interviews, direct observation, and document analysis involving stakeholders such as medical staff, administrators, and IT personnel. The findings indicate that while users acknowledge improvements in data accuracy and accessibility, key issues remain, particularly in training quality, infrastructure readiness, and system reliability. The study also observed gradual improvements in SOP compliance and reduced system failures over time. These results suggest that successful EMR adoption requires a balance of technical infrastructure, human resource readiness, financial support, and continuous system monitoring. The use of the 5M framework proved effective in identifying multidimensional challenges and offering holistic insights into the implementation process. This study contributes to the broader literature on EMR evaluation by providing contextualized evidence from a district-level hospital and offers practical recommendations for enhancing EMR system performance in similar healthcare settings.